Arachniodes mira (Dryopteridaceae), a new species from southeastern Yunnan, China - Wei, Hong-Jin (Phytotaxa, 2025)
Arachniodes mira, a new sexual diploid species of Dryopteridaceae from southeastern Yunnan, China, is described and illustrated. This species is unique within the genus for its fronds transitioning from pinnate with a caudate-acuminate apex when young to either imparipinnate or to bipinnate with a terminal pinna when mature. This new species may have arisen from hybridization between A. neopodophylla and an unknown bipinnate species, displaying a combination of morphological features between these two species. The only found population is facing with extinction due to habitat destruction.